Effect of hydroxychloroquine in viral clearance in nCOV-19 infected patient admitted in tertiary care centre, Ranchi, Jharkhand, India - Mishra, Brajesh; Munda, Manish K.; Dungdung, Ajit; Ekka, Nishit M. P.; Prasad, Manoj K.; Kumar, Prabhat; Kumar, Abhay; Guria, Rishi T.; Bakhla, Ajay K. (International Journal of Research in Medical Sciences, 2020)
Background: In view of recent publications of conflicting evidence on the safety and efficacy of hydroxychloroquine as prophylaxis and as a treatment for COVID-19 patients, we need to assess the effect of hydroxychloroquine in COVID-19 patients of authors own local population. Methods: In this retrospective chart review study, categorization of confirmed COVID-19 cases nasopharyngeal swab of RT-PCR was done into a group of patients who received hydroxychloroquine standard dose and another control group who did not receive hydroxychloroquine. The main comparing parameter was to see virus clearance days across both groups. Results: A total of 112 patients were included for the study, and grouped of 72 patient who received HCQS and remaining 40 patients as control. The virus clearance time in days was found to be 9.01±3.08 for HCQS group and for control group it was 8.64±2.34 days (Man Whitney U test value = 2.13, p=0.756). Conclusions: There is no significant difference found in attaining virus negative status with use of HCQS administration in this study.